Principles and Rules for Determining the Tax Capacity of Entrepreneurs in Income Taxes - Supera-Markowska, Maria (Journal of Finance and Financial Law, 2022)
The purpose of this paper is a multifaceted theoretical and legal analysis of the issue of determining the tax capacity of entrepreneurs in income taxes so as to be able to assess the adequacy of the rules in this area for the proper implementation of this concept. The research hypothesis assumes that these rules currently in force, to a large extent, do not ensure proper implementation of the concept of tax capacity, especially in the conditions of the digitalized and globalized economy, but also in times of progressive development of instruments to counteract not only tax evasion but also tax avoidance. Therefore, it is necessary to change them in many aspects. The research was carried out using a dogmatic and comparative legal method, taking into account in particular the provisions of domestic, foreign and EU laws, the body of domestic and foreign tax law literature, court rulings and proposals for new tax and legal solutions put forward on the EU and international forum. The analysis took into account the essence of the tax capacity concept and closely related tax principles, as well as the functions of taxes, both in the national and international context. The results of the research is the formulation of some conclusions as to the desirable guidelines for determining the rules for measuring the tax capacity of entrepreneurs in income taxes, which should be related to the fundamental concept of tax capacity and the principles of equity and neutrality of taxation. Currently, these principles are violated in many national, as well as international aspects, i.a. by deviating from the criteria of income as an indicator of tax capacity. In this context a very important distinction should be made between situations where the abandoning of the determination of income of entrepreneurs is justified by the pursuit of a fair distribution of the tax burden (as, e.g., in case of so-called digital tax) and situations when it results from the desire to achieve certain non-fiscal goals. In such a case, any variation in those rules must be assessed on a case-by-case basis as to whether it is justified. On the other hand, in the former case, even temporarily – especially in the international aspect – until international solutions are worked out, it may even be indispensable to differentiate the rules for determining the tax capacity of entrepreneurs (e.g. abandoning the criterion of income in favor of revenue in digital tax) precisely in order to ensure fair and neutral taxation. In this context, it is worth noting that some of the problems underlying these different approaches may be solved by a comprehensive reform of the rules for determining the tax capacity of entrepreneurs, to be developed both internationally within the OECD and in the EU within BEFIT. It should also not be underestimated that in these projects the fundamental categories and concepts are those of balance sheet law, including in particular the proposed adoption of the concept of adjusted financial result for the purposes of determining the tax result. Taking into account this issue and also in a view of the increasing development of general tax law norms aimed at minimizing the phenomena of tax avoidance and optimization, it seems worth considering an increasing possibility that the tax capacity of entrepreneurs should be determined by its natural measure, i.e. the financial result of their business activity.